Population-Based and Personalized Design of Total Knee Replacement Prosthesis for Additive Manufacturing Based on Chinese Anthropometric Data. (March 2021) - Chui, C.S.; Leung, K.S.; Qin, J.; Shi, D.; Augat, P.; Wong, R.M.Y.; Chow, S.K.H.; Huang, X.Y.; Chen, C.Y.; Lai, Y.X.; Yung, P.S.H.; Qin, L.; et al.
Abstract: At present, most total knee replacement (TKR) prostheses on the market are designed according to the sizes of Caucasians. However, extensive studies have indicated that human anatomies differ among different ethnicities. A number of reports have indicated that Chinese TKR patients do not match with available prostheses. In this study, computed tomography (CT) images of 52 knees of Chinese men and women were used for anthropometric measurements. Index and geometric measurements were defined and used for correlation analysis. Key parameters from the measurement results were identified. Detailed geometries of knees were measured as coordinates. A deformable three-dimensional (3D) knee model based on anatomical coordinates correlating with the identified key parameters was generated. A prosthesis was then designed according to the analyzed results. Surface matching analysis, bone resection analysis, and cadaveric trials were conducted and compared with commercial products to validate the proposed design. The femoral component designed by this study resulted in the highest accuracy (root mean square point-to-surface (RMS PS), (1.08 ± 0.20) mm) and lowest amount of resected bone volume (27 412 mm 3 ) in comparison with two commercial knee prostheses. This study suggests a new approach for population-based patient-specific femoral prosthesis design. With a single, easily acquired dimension—namely, epicondyle width (ECW)—as input, a patient-specific femoral prosthesis can be designed according to the analyzed measured data and manufactured by additive manufacturing (AM) methods. Meanwhile, the reconstructed femoral condylar surface was compared with the femoral condylar surface in the original CT scanning data. The average RMS PS distance of the reconstructed femoral condylar surface among all data was (1.10 ± 0.18) mm, which is comparable to other statistical shape modeling methods using multiple radiographs as input data. There is a need to develop an anthropometric-based knee prosthesis for the Chinese population. Based on the anthropometry of the Chinese population, our new design fits Chinese patients better and reserves more bone volume compared with current commercial prostheses, which is an essential step toward AM for personalized knee prostheses.